An information classification model for public sector organizations in Sweden: a case study of a Swedish municipality. (16th August 2021) - Bergquist, Jan-Halvard; Tinet, Samantha; Gao, Shang
Abstract : Purpose: The purpose of this study is to create an information classification model that is tailored to suit the specific needs of public sector organizations in Sweden. Design/methodology/approach: To address the purpose of this research, a case study in a Swedish municipality was conducted. Data was collected through a mixture of techniques such as literature, document and website review. Empirical data was collected through interviews with 11 employees working within 7 different sections of the municipality. Findings: This study resulted in an information classification model that is tailored to the specific needs of Swedish municipalities. In addition, a set of steps for tailoring an information classification model to suit a specific public organization are recommended. The findings also indicate that for a successful information classification it is necessary to educate the employees about the basics of information security and classification and create an understandable and unified information security language. Practical implications: This study also highlights that to have a tailored information classification model, it is imperative to understand the value of information and what kind of consequences a violation of established information security principles could have through the perspectives of the employees. Originality/value: It is the first of its kind in tailoring an information classification model to the specific needs of a Swedish municipality. The model provided by this study can be used as a tool to facilitate a common ground for classifying information within all Swedish municipalities, thereby contributing the first step toward a Swedish municipal model for information classification.